Bedload transport within a patchy submerged canopy with different patch densities and spatial configuration - Park, Hyoungchul; Nepf, Heidi (Frontiers in Marine Science, 2025)
This study conducted laboratory experiments to investigate the bedload transport within a patchy submerged canopy across a range of patch area densities and spatial configurations. The patch area densities (ϕp), defined as the bed area fraction covered by patches, ranged from 0 to 0.56, while the spatial configurations varied from channel-spanning patches to laterally unconfined patches. At low area density (ϕp<0.3), as ϕp increased, more flow passed over the top of the canopy, decreasing the near-bed velocity. However, the formation of turbulent wakes around individual patches increased the near-bed turbulent kinetic energy (TKE). These opposing trends led to a mild decrease in the bedload transport rate with increasing ϕp. In contrast, at high area density (ϕp>0.3), both near-bed velocity and TKE decreased with increasing ϕp, resulting in a sharp decrease in bedload transport rate. Furthermore, at the same ϕp, channel-spanning patches were associated with lower bedload transport, compared to laterally unconfined patches. A predictive model for bedload transport rate that incorporated both near-bed mean velocity and TKE provided more accurate predictions than models based only on time-averaged velocity (bed stress) or TKE.